Human herpesvirus 6 DNA was not detected in a brain specimen from a patient with mesial temporal sclerosis after status epilepticus due to human herpesvirus 6 infection. Issue 4 (23rd August 2022) - Kawamura, Yoshiki; Maesawa, Satoshi; Numoto, Shingo; Saito, Ryuta; Yoshikawa, Tetsushi; Okumura, Akihisa
Abstract: We performed virological analysis of resected brain tissues from a patient with temporal lobe epilepsy associated with mesial temporal sclerosis after febrile status epilepticus caused by human herpesvirus 6 infection. The patient had febrile status epilepticus at 9 months of age associated with human herpesvirus 6 infection. Magnetic resonance imaging revealed reduced water diffusion in the right temporal lobe and hippocampus. Polymerase chain reaction analysis detected 1.6 × 10 5 copies/μg of human herpesvirus 6 DNA in whole blood, but none in the cerebrospinal fluid. The patient developed temporal lobe epilepsy associated with mesial temporal sclerosis at 67 months of age, necessitating surgical treatment. Anterior temporal lobectomy was performed at 171 months of age. Real‐time polymerase chain reaction analysis of resected brain tissues revealed no viral DNA. In our patient, human herpesvirus 6 infection triggered febrile status epilepticus, while direct evidence to prove contribution of HHV‐6 to the development of MTS was not obtained.